Worlds of Junípero Serra : historical contexts and cultural representations - Hackel, Steven W. (Western histories ;, 2018)
"In September 2015, Junípero Serra was canonized by Pope Francis in Washington DC against the protest of many Californian Native Americans who criticized his brutal treatment of their ancestors and destruction of their culture. Like most complex historical figures, Junípero Serra has been interpreted in countless ways, often contextualized mainly in California. This book situates Serra in the context of the three major places that he lived, learned, and proselytized: Mallorca, Mexico, and Alta California. Scholars from all three countries contribute to a rare glimpse into the life of the saint by considering his use of music and art, his representation in popular culture; his education, ideology, and Franciscan influence; the plans and building of the missions; and his relation to native peoples."--Provided by publisher.